Dismantling Strategy in Post-Structural Criticism and Undermining Mechanisms - Soltani, Farouk (Dirasat: Human and Social Sciences, 2022)
Deconstructionism that (Jacques Derrida) looked at in the 1960S is a strategy for reading and undermining texts. Deconstructionism has emerged at the postmodernism stage as an anti-revolutionary reaction against structural approaches; this is because Derrida’s deconstructionism appears as an extension of post-structural criticism, which is based on releasing the texts from the mental constants and disrupting the system that is based on, and it undermines the cultural patterns on which modern literary discourse is based on, which makes its meaning has multiple and different indications from reading to another and from one context to another. Deconstructionism is based on her study of literary texts on a group of undermining mechanisms which try to talk about in this article titled: dismantling strategy in post-structural criticism and undermining mechanisms.